The better blend? Flipping the principles of microeconomics classroom. (January 2016) - Olitsky, Neal H.; Cosgrove, Sarah B.
Abstract: This study provides a comprehensive analysis of an experiment that attempts to cut costs and improve learning outcomes through a "flipped-blended" class. We discern effects of this pedagogy on learning outcomes in principles of microeconomics courses. We control for key background variables and use differences-in-differences with a matching estimator to test whether students in the flipped-blended classes learn economic concepts and tools better than students in classes with interactive lectures and online homework, but no online lectures. Findings suggest that average student improvement is significantly higher in flipped classes than in non-flipped classes, though the difference in improvement is modest.